Recent advances in compact repetitive high-power Marx generators. (3rd April 2019) - Song, Falun; Li, Fei; Zhang, Beizhen; Zhu, Mingdong; Li, Chunxia; Wang, Ganping; Gong, Haitao; Gan, Yanqing; Jin, Xiao
Abstract: This paper introduces recent activities on Marx-based compact repetitive pulsed power generators at the Institute of Applied Electronics (IAE), China Academy of Engineering Physics (CAEP), over the period 2010–2018. A characteristic feature of the generators described is the use of a simplified bipolar charged Marx circuit, in which the normal isolation resistors or inductors to ground are removed to make the circuit simpler. Several pulse-forming modules developed to generate a 100 ns square wave output are introduced, including thin-film dielectric lines of different structures, a pulse-forming line based on a Printed Circuit Board, and non-uniform pulse-forming networks. A compact repetitive three-electrode spark gap switch with low-jitter, high-voltage, and high-current was developed and is used in the generators. A positive and negative series resonant constant current power supply with high precision and high power is introduced. As an important part of the repetitive pulse power generator, a lower jitter pulse trigger source is introduced. Several typical high-power repetitive pulsed power generators developed at IAE are introduced including a 30 GW low-impedance Marx generator, a compact square-wave pulse generator based on Kapton-film dielectric Blumlein line, a 20 GW high pulse-energy repetitive PFN-Marx generator, and a coaxial Marx generator based on ceramic capacitors. The research of key technologies and their development status are discussed, which can provide a reference for the future development and application of miniaturization of compact and repetitive Marx generators.